Kenoto Adat Perkawinan Suku Sabu, Kajian Sosiologi Agama dalam Tindakan Sosial Max Weber - Alyan Maurits Sioh (Universitas Negeri Medan, 2020)
The purpose of this study is to explain the importance of the Kenoto marriage and the noble values that exist in the kenoto marriage. The research used is qualitative research to see Kenoto as a unifying tool in the Sabu tribal community. The Kenoto Ritual in the Customs of Sabu Tribal Marriage Max Weber's Sociology of Religion Study in Social Action. The method of observation and structured interviews. The analyzed are the results of interviews and observations with Indigenous and church leaders, Religious Leaders and Marriage Couples. The results showed that the priority of the Kenoto marriage in the Sabu tribal community was very important and became the basis. Because the Kenoto Marriage shows the self-esteem of a woman. To better understand comprehensively, this analysis will provide answers through a typical understanding of Weber's social action theory, the type of social action that is suitable or used in the kenoto marriage, namely Traditional Action and Value Rationality.